2019
DOI: 10.1097/pas.0000000000001315
|View full text |Cite
|
Sign up to set email alerts
|

Application of a 5 Marker Panel to the Routine Diagnosis of Peripheral T-Cell Lymphoma With T-Follicular Helper Phenotype

Abstract: The 2017 World Health Organization update introduced a new category of nodal peripheral T-cell lymphoma with T-follicular helper phenotype (PTCL-TFH) defined by expression of at least 2 or 3 TFH markers. Our study assesses the utility of an immunohistochemical panel of 5 TFH markers (CD10, BCL6, PD-1, CXCL13, and ICOS) for identification of TFH phenotype in angioimmunoblastic T-cell lymphoma (AITL) and PTCL not otherwise specified (NOS). Immunohistochemical for the 5 markers was performed on 22 cases of AITL a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 37 publications
4
36
0
Order By: Relevance
“…Interestingly, the majority of CD30 hi Tfh cells were expressing a BCL6 hi phenotype too, indicating a possible role of CD30 in the differentiation process of AITL Tfh cells. Although the WHO criteria specifically state that expression of at least three Tfh markers is required for assignment of a Tfh phenotype (38,95), we detected a high level of heterogeneity concerning six Tfh markers, which were robustly co expressed in the tumor niche, that is to say CD4, PD-1, CXCR5, ICOS, Bcl6, and CXCL13. In a recent study, two AITL cases were analyzed using multiplexed quantitative immunohistochemistry techniques and one panel to simultaneously stain for a collection of relevant markers in lymphoid tissue to determine the expression of marker of interest in malignant cells, such as the CD4, PD-1, and BCL6.…”
Section: Discussionmentioning
confidence: 77%
“…Interestingly, the majority of CD30 hi Tfh cells were expressing a BCL6 hi phenotype too, indicating a possible role of CD30 in the differentiation process of AITL Tfh cells. Although the WHO criteria specifically state that expression of at least three Tfh markers is required for assignment of a Tfh phenotype (38,95), we detected a high level of heterogeneity concerning six Tfh markers, which were robustly co expressed in the tumor niche, that is to say CD4, PD-1, CXCR5, ICOS, Bcl6, and CXCL13. In a recent study, two AITL cases were analyzed using multiplexed quantitative immunohistochemistry techniques and one panel to simultaneously stain for a collection of relevant markers in lymphoid tissue to determine the expression of marker of interest in malignant cells, such as the CD4, PD-1, and BCL6.…”
Section: Discussionmentioning
confidence: 77%
“…Although the exact frequency of the disease is unknown, Basha et al reported that approximately 40% of the cases diagnosed as PTCL-NOS could be re-classified as nodal PTCL, using the these markers. 10 Proliferation with mainly follicular growth pattern is characteristic to FTCL, and this is its point of differentiation from PTCL-NOS. 1 Primary cutaneous CD4 + small/medium T-cell lymphoproliferative disorder is an excellent prognosis lesion, which often appears as a single skin lesion; its common sites are the face, neck, and upper trunk.…”
Section: Discussionmentioning
confidence: 99%
“…1 In particular, PD‐1 with high sensitivity and CXCL13 with high specificity were useful immunophenotypic markers of neoplastic T cells in AITL. 1 , 6 In contrast, there were no reports of AITL lymphomatous effusion diagnosed by cell block immunohistochemistry. Our findings related to atypical lymphoid cells immunoreactivity for TFH‐cell markers on the cell block sections, and our cytologic findings, were useful for the definitive diagnosis of lymphomatous effusion caused by AITL.…”
Section: Figurementioning
confidence: 99%